Navigating Power and Politics: Strategic Competence as a Predictor of Women’s Electoral Success in the Philippines - Boniel, Almira (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the strategic competence of women in Philippine politics that contributed to success in electoral campaigns, focusing on former Presidents Corazon Cojuangco Aquino and Gloria Macapagal-Arroyo. Anchored on Longwe’s Women Empowerment framework, the study analyzed women’s leadership in terms of welfare, access, conscientization, participation, and control, particularly in relation to political representation, electoral strategy, governance, and empowerment. Using a qualitative historical research design, the study relied on secondary sources such as electronic articles, e-books, speeches, e-journals, related studies, literature books, news recordings, and other documented materials. No respondents or participant sampling were involved. Data were examined through historical data analysis, content analysis, and document review. Findings showed that both Aquino and Arroyo met the constitutional qualifications for the presidency and demonstrated strategic competence through advocacy, personal attributes, political participation, execution of campaign functions, and electoral mechanisms. Aquino’s success was linked to democratic restoration, moral integrity, human rights advocacy, coalition building, symbolism, grassroots engagement, and mass mobilization. Arroyo’s success was associated with strategic coalition building, pragmatic policy agenda-setting, political machinery, unity and stability messaging, economic development, voter outreach, media management, and policy advocacy. The study concludes that women’s success in Philippine electoral politics depends not only on formal qualifications but also on strategic campaign competence and the ability to connect leadership identity with public needs and voter aspirations. The study is most directly aligned with SDG 5 on Gender Equality and SDG 16 on Peace, Justice, and Strong Institutions, with related connections to education, health, economic growth, communities, and partnerships. Its sustainability impact lies in strengthening understanding of women’s leadership, democratic participation, institutional reform, and inclusive governance.
Keywords: Aquino; Arroyo; Electoral Campaigns; Gender Equality; Longwe’s Women Empowerment Framework; Philippine Politics; Political Participation; Strategic Competence; Women’s Leadership